Bhutan : 2011 Article IV Consultation-Staff Report; Staff Supplement; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Bhutan. (IMF Staff Country Reports; Country Report, 2011)
Bhutan's rapid growth has been underpinned by hydropower sector development with donor support. However, fiscal policy should be tightened to address overheating, and spending and revenue reforms are needed to bolster the fiscal framework. Executive Directors suggested to adopt multiyear rolling budget to ensure debt sustainability. They assessed the need to strengthen the Royal Monetary Authority (RMA's) power to safeguard financial stability. They welcomed the comprehensive strategy embedded in the Economic Development Policy (EDP) that identifies activities that have strong job-generating potential and also promote foreign direct investment and private sector development.